Unaccompanied foreign minors and education: a bibliometric analysis of the international academic literature - Serrano-García, Jennifer; Rakdani-Arif Billah, Fátima Zahra; Expósito-López, Jorge; Olmedo-Moreno, Eva Mª (Frontiers in Education, 2025)
IntroductionThe migration of unaccompanied foreign minors presents a significant global educational and social challenge. This study aims to analyze the international scientific production on UFM in the educational field, identifying key trends, influential authors, and institutional contributions.MethodsA bibliometric analysis was conducted using data from the Web of Science and Scopus databases, applying rigorous inclusion and exclusion criteria to ensure the relevance of selected studies.ResultsThe findings reveal that research on UFM in education is limited, with publications concentrated in a few high-impact journals and led by a small group of prolific authors. The results align with Bradford’s and Lotka’s laws, demonstrating an uneven distribution of research outputs and the dominance of a few institutions, particularly the University of Granada. Thematic analysis highlights a focus on academic self-efficacy, employability skills, social inclusion, and digital competencies.ConclusionHowever, gaps remain in understanding teachers’ perceptions of UFM and the impact of educational policies on their integration. Addressing these gaps is essential to fostering inclusive education and informing policy development. Future research should prioritize teacher training programs to challenge stereotypes and implement strategies that enhance digital inclusion and social integration for this vulnerable population.